2011
DOI: 10.1242/jcs.081000
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of afadin in barrier function and homeostasis of mouse intestinal epithelia

Abstract: Afadin interacts with the cytoplasmic region of nectins, which are immunoglobulin-like cell adhesion molecules at adherens junctions, and links them to the actin cytoskeleton. Afadin regulates activities of cells in culture such as directional motility, proliferation and survival. We used Cre-loxP technology to generate mice conditionally lacking afadin specifically in the intestinal epithelia after birth. The loss of afadin caused increased paracellular permeability in the intestinal mucosa and enhanced susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 47 publications
6
47
1
Order By: Relevance
“…In vitro studies have suggested that afadin is necessary for recruitment of cadherins to apical junctions in epithelia (Ooshio et al, 2007), but in vivo studies of intestinal epithelial development have not shown similar results (Tanaka-Okamoto et al, 2011). Rcadherin expression is upregulated in renal vesicles (Dahl et al, 2002), and it may be the predominant cadherin expressed at this stage (Brunskill et al, 2008).…”
Section: Afadin Is Necessary For R-cadherin and Actin Recruitment To mentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies have suggested that afadin is necessary for recruitment of cadherins to apical junctions in epithelia (Ooshio et al, 2007), but in vivo studies of intestinal epithelial development have not shown similar results (Tanaka-Okamoto et al, 2011). Rcadherin expression is upregulated in renal vesicles (Dahl et al, 2002), and it may be the predominant cadherin expressed at this stage (Brunskill et al, 2008).…”
Section: Afadin Is Necessary For R-cadherin and Actin Recruitment To mentioning
confidence: 99%
“…Mice that lack afadin have defects in gastrulation and disorganization of the ectoderm (Ikeda et al, 1999). More recently, conditional deletion of afadin from intestinal epithelia has shown that afadin is essential for recruiting nectins to apical junctions and for maintaining barrier function (Tanaka-Okamoto et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These proteins can form junctions independently from one another; nectin junctions assemble in cadherin-deficient cells , and cadherin junctions are formed, albeit with reduced kinetics, in nectin-inactivated cells (Sato et al, 2006;Tanaka-Okamoto et al, 2011;Indra et al, 2014). In adherens junctions, cadherin and nectin are located in separate, yet closely associated, adhesive clusters (Indra et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibitors of nectin adhesion or afadin knockdown slow the formation of cadherin adhesive clusters in a Ca 2+ -switch assay (Sato et al, 2006;Lorger and Moelling, 2006) or between two cells upon coming into contact with one another (Indra et al, 2014). However, this defect in the kinetics of adherens junction formation does not affect the general appearance of cell-cell adhesion contacts, including the ultrastructural features of adherens junctions (Zhadanov et al, 1999;Sawyer et al, 2009;Tanaka-Okamoto et al, 2011). Therefore, the available data show that nectin facilitates the formation of adherens junctions, but it is involved neither in the basic mechanisms of their assembly nor in their structural organization.…”
Section: Introductionmentioning
confidence: 99%
“…Another major adhesion molecule in AJs is nectins, which bind to an actin-binding protein AF6/ afadin at their cytoplasmic region (37 -38). Because afadin knockout in mouse intestinal epithelial cells showed no change in junctional and epithelial organization, importance of actin filament/ afadin association in AJ is limited (39). Eplin is colocalized with actin filaments within cells and also found in ZAs but not in PAs, also showing its limited function in AJ formation (12,40,41).…”
Section: Aj Components Responsible For Actin As-sociationmentioning
confidence: 99%